2004
DOI: 10.1007/s00436-004-1264-8
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro anti-giardial activity of extracts from plants that are used for self-medication by AIDS patients in southern Thailand

Abstract: This study evaluated the anti-giardial activity of chloroform, methanol and water extracts of 12 medicinal plants (39 extracts), commonly used as self medication by AIDS patients in southern Thailand. The plant extracts and a standard drug, metronidazole, were incubated with 2x10(5) trophozoites of Giardia intestinalis per millilitre of growth medium in 96-well tissue culture plates under anaerobic conditions for 24 h. The cultures were examined with an inverted microscope and the minimum inhibitory concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 29 publications
1
52
0
Order By: Relevance
“…However, all of these drugs are reported to have unpleasant side effects, and potential carcinogenic, teratogenic, and embryogenic questions have been addressed (Friedman, 1980;Davidson, 1990). In addition, some strains of G. lamblia have developed resistance to some of these remedies (Sawangjaroen et al, 2005). Nowadays, the effectiveness of alternative anti-parasitic treatments is extremely important, and by the way, there is resurgence in the use of natural alternative therapies instead of synthetic pharmaceuticals that often have severe side effects as mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…However, all of these drugs are reported to have unpleasant side effects, and potential carcinogenic, teratogenic, and embryogenic questions have been addressed (Friedman, 1980;Davidson, 1990). In addition, some strains of G. lamblia have developed resistance to some of these remedies (Sawangjaroen et al, 2005). Nowadays, the effectiveness of alternative anti-parasitic treatments is extremely important, and by the way, there is resurgence in the use of natural alternative therapies instead of synthetic pharmaceuticals that often have severe side effects as mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sawangjaroen et al (2005Sawangjaroen et al ( , 2006 evaluated the in-vitro activity of selected medicinal plants used in a primary health care project by AIDS pa-In India, the traditional folklore healthcare system has a long history and is very deeply rooted in rural and tribal populations. India has medicinal plants distributed in different geographical and environmental conditions (Chandler et al 1979, Katewa 2009).…”
Section: Phytochemistry Of Ethnomedicinal Plants: Implications In DIVmentioning
confidence: 99%
“…In the similar studies has been suggested to identify the compounds responsible for the anti-giardial activities in the chloroform leaf extracts of P. betle and P. chaba (17)(18)(19). According to current research and so, isolated bioactive compounds from plants were utilized against a wide range of microorganisms particularly parasites.…”
Section: Introductionmentioning
confidence: 99%